Epidemiology of medullary thyroid carcinoma - Raue, Friedhelm (Medullary thyroid carcinoma, 1992)
Medullary thyroid carcinoma (MTC) was first recognized as a distinct pathological entity by Hazard et al. (1959), who, out of 600 cases of thyroid cancer, identified 21 cases of this tumor from its histopathological appearance. MTC originates from the thyroid parafollicular C-cells first suggested by Williams (1967) and secretes large amounts of calcitonin, a feature which has been used for diagnosis since 1970. MTC is a rare disease which occurs in a sporadic and a familial form; the familial variant is inherited in an autosomal dominant trait associated with other endocrine tumors (multiple endocrine neoplasia, MEN). The combination of MTC with adrenal medullary tumor and parathyroid tumor (MEN 2A) was first described in 1961 by Sipple. A second variant, MEN 2B, consists of MTC, pheochromocytoma, neural tumors, and a marfanoid habitus. The third variety of MTC is the non-MEN familial MTC, a hereditary MTC without any other endocrinopathies.